PENYULUHAN MENINGKATKAN PENGETAHUAN KEPALA DESA DAN BPD TENTANG MANAJEMEN PENGELOLAAN DAN PENGAWASAN KEUANGAN DESA DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Hadiawan, Agus; Syafarudin, Syafarudin; Dwijono, Amantoto; Warganegara, Arizka; Purba, Darmawan (Prosiding Pengabdian FISIP Unila, 2012)
Extension  took place on  July 10, 2012  at  district  hall   Natar,  South  Lampung regency. Participants  came from 22 villages  in the  district Natar. Village  heads were 18 people  present, who  have as a deputy  4 people  (sekdes  or staff). While BPD was attended by the chairman or members of the BPD. The results and conclusions of this service activities are: (a) counseling given was to increase  the knowledge  and  attitude of  the head of  the village  head  and  the village of BPD on financial management as set forth in Permendagri 37 of 2007 as well as  their  efforts to  resolve  the conflict management and  financial control of the village by way of dialogue or deliberation;  (b)  the level of knowledge of the head of the village head and BPD financial management of the village as provided in Permendagri 37 of 2007 initially low, but after the extension increases the level of  their  knowledge, (c)  the attitude of  the village head and  BPD  attitude  that prioritizes  dialogue  and deliberation  to resolve the conflict  management and financial control of the village of approval  than before held counseling. Keywords: Financial Management of Rural Management, APBDesa